Prunus Recent Advances - Küden, Ayzin B.; Küden, Ali (IntechOpen, 2022)
Prunus is one of the most important genera of fruit. It includes peaches, plums, cherries, apricots, and other stone fruits. This book discusses breeding, germplasm, fruit tree physiology, pruning, production, and nutritional studies of the Prunus species. It includes two sections on "Molecular and Breeding Studies and Germplasm Diversity in Prunus Species" and "Physiological and Nutritional Studies on Prunus Species."